Kekerasan Seksual Terhadap Anak: Analisis Relasi Pelaku-Korban dan Dampaknya Terhadap Anak sebagai Korban - Utami, Feby Reski; Irawan, Benny; Maulana, M. Ramzi (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
Cases of sexual violence against children in Indonesia have shown a significant increase in both quantity and severity. Most perpetrators are found to be individuals within the victim’s close environment such as family members, teachers, or community figures, making the issue more complex to address. This study aims to analyze the relationship between perpetrators and victims and the resulting impacts on children as victims of sexual violence. The research employs a normative juridical method with statutory and case approaches. Data were collected through a literature study by reviewing relevant regulations, including Law No. 17 of 2016 on Child Protection and Law No. 12 of 2022 on Sexual Violence Crimes. The findings reveal that children are a highly vulnerable group due to their dependence and power imbalance with adults. The impacts of sexual violence include physical, psychological, emotional, and social consequences, such as trauma, depression, fear, and difficulty forming social relationships. The study concludes that effective prevention and law enforcement require collaboration among families, educational institutions, communities, and the state. Strengthening legal protection and implementing rehabilitation for victims are strategic steps toward achieving justice and restoring the rights of children as the nation’s future generation. Keywords: sexual violence, children, criminal law, child protection, psychological trauma